2016
DOI: 10.1111/cpf.12400
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme 2 polymorphisms and postexercise hypotension in hypertensive medicated individuals

Abstract: The renin-angiotensin aldosterone system (RAAS) is associated with diverse physiological responses and adaptations to exercise. The angiotensin converting enzyme (ACE) 2 has vasodilatory effects, which might be associated with the blood pressure (BP) responses to acute exercise. The aim of this study was to investigate the role of ACE2 polymorphisms in postexercise hypotension (PEH). Thirty-four medicated hypertensive (61·3 ± 1·7 years, 76·1 ± 2·7 kg, 160 ± 1·6 cm) men (n = 12) and women (n = 22), participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…In addition, Goessler et al investigated the role of ACE2 polymorphisms in PEH and observed a significant reduction in SBP and DBP following exercise in individuals AA/AG for the Int-1 polymorphism (p-interaction = 002 and 0001, respectively), whereas this could not be found in homozygous individuals G (p-interaction = 076 and 051, respectively). 38 Individuals AA/AG for the Int-3 polymorphism showed a significant reduction in SBP following exercise (p-interaction = 0.02). These results demonstrated the interference of ACE2 polymorphism in PEH.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Goessler et al investigated the role of ACE2 polymorphisms in PEH and observed a significant reduction in SBP and DBP following exercise in individuals AA/AG for the Int-1 polymorphism (p-interaction = 002 and 0001, respectively), whereas this could not be found in homozygous individuals G (p-interaction = 076 and 051, respectively). 38 Individuals AA/AG for the Int-3 polymorphism showed a significant reduction in SBP following exercise (p-interaction = 0.02). These results demonstrated the interference of ACE2 polymorphism in PEH.…”
Section: Discussionmentioning
confidence: 98%
“…Our subjects were not taking anti-hypertensive medications, whereas most studies of PEH in hypertensive individuals have included subjects on blood pressure medications ( Melo et al, 2006 ; Brito et al, 2011 ; Cunha et al, 2016 ; Cunha et al, 2017 ; Ferrari et al, 2017 ; Imazu et al, 2017 ; Cunha et al, 2018 ; Goessler et al, 2018 ; de Freitas Brito et al, 2019 ; Costa et al, 2020 ; Pires et al, 2020 ). Thus, our results may not be applicable to those taking anti-hypertensive medications.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of PEH is positively related to the baseline BP prior to exercise (Brito et al, 2018). Indeed, PEH has been repeatedly demonstrated in hypertensive populations (Legramante et al, 2002;Melo et al, 2006;Brito et al, 2011;Dos Santos et al, 2014;Cunha et al, 2016;Cunha et al, 2017;Ferrari et al, 2017;Imazu et al, 2017;Cunha et al, 2018;Goessler et al, 2018;de Freitas Brito et al, 2019;Pires et al, 2020;Iellamo et al, 2021). However, in virtually all of these studies the hypertensive populations included individuals with and without obesity, with mean BMI < 30 kg/m 2 in most instances.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados en este estudio se asemejan a los encontrados en población adolescentes franco-canadienses 20 , australianos 14 y chinos 21 , lo que podría indicar que el polimorfismo (rs1978124) de la ACE2 no tiene un impacto importante en los cambios de la presión sanguínea en sujetos sedentarios en contraposición con otros polimorfismos del mismo gen 15,22 . Sin embargo, la mayoría de esos estudios analizan las variables hemodinámicas en sujetos con algún tipo de patología cardiovascular 16,21,23 , lo que significa que el sistema ya se encuentra expuesto a una condición de estrés basal. Este último factor, pudiese acentuar el papel que juega la ACE y ACE2 en la modulación de la respuesta hemodinámica frente a un estímulo, evidenciando diferencias en variables como la presión arterial.…”
Section: Discussionunclassified